2011
DOI: 10.1002/hipo.20812
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic hypofunction impairs memory acquisition possibly through hippocampal Arc and BDNF downregulation

Abstract: Recent evidence suggests that activity-regulated cytoskeleton associated protein (Arc) and brain-derived neurotrophic factor (BDNF) are key players in the cellular mechanisms that trigger synaptic changes and memory consolidation. Cholinergic deafferentiation of hippocampus has been largely shown to induce memory impairments in different behavioral tasks. However, the mechanisms underlying cholinergic-induced memory formation remain unclear. The role of hippocampal cholinergic denervation on synaptic consolida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 49 publications
5
31
0
Order By: Relevance
“…This is consistent with previous studies showing that a complete lesion of BFCNs in rats resulted in reduced BDNF mRNA in the hippocampus (Kokaia et al, 1996, Ferencz et al, 1997, Berchtold et al, 2002 and that cholinergic basal forebrain innervation of hippocampus is involved in the regulation of BDNF protein and mRNA (Lapchak et al, 1993, Gil-Bea et al, 2011. BDNF is synthesized, stored and released from dendrites of most excitatory neurons including pyramidal neurons in the hippocampus, in an activity-dependent manner (Hartmann et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with previous studies showing that a complete lesion of BFCNs in rats resulted in reduced BDNF mRNA in the hippocampus (Kokaia et al, 1996, Ferencz et al, 1997, Berchtold et al, 2002 and that cholinergic basal forebrain innervation of hippocampus is involved in the regulation of BDNF protein and mRNA (Lapchak et al, 1993, Gil-Bea et al, 2011. BDNF is synthesized, stored and released from dendrites of most excitatory neurons including pyramidal neurons in the hippocampus, in an activity-dependent manner (Hartmann et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…ACh mediates hippocampal learning and memory through regulation of long-term potentiation (LTP) and synaptic consolidation (Auerbach and Segal, 1994, Ovsepian et al, 2004, Drever et al, 2011. Moreover, ACh is a presynaptic modulator of hippocampal excitatory transmission, promoting long-term synaptic plasticity and upregulating brain-derived neurotrophic factor (BDNF) protein and Arc expression in the hippocampus, which are involved in synaptic consolidation (Fernandez de Sevilla et al, 2008, Gil-Bea et al, 2011. Thus ACh signalling from the cholinergic basal forebrain to the hippocampus is vital for hippocampal function and normal cognition, and deterioration of this brain structure in human disease, not surprisingly, has devastating consequences.…”
Section: The Cholinergic Basal Forebrainmentioning
confidence: 99%
See 2 more Smart Citations
“…Initiated by the pioneering work of MacIntosh and Oboring (1955), which demonstrated that ACh controls the neuronal excitability, the interest in the function of the cholinergic system greatly increased with the characterization of cholinergic antagonists as impairment agents of cognitive abilities (Deutsch, 1971;Drachman, 1977) and with the postmortem identification of reduced cholinergic markers in the brain of Alzheimer's disease patients (Bowen et al, 1976;Perry et al, 1978). The cholinergic drive controls a large variety of cognitive processes, such as attention (Hasselmo and Sarter, 2011), learning (Fine et al, 1997;Miranda and Bermú dez-Rattoni, 1999), and memory (Hasselmo and Bower, 1992;Gil-Bea et al, 2010) by boosting the signal-to-noise ratio (Sillito and Kemp, 1983) in various cortical and subcortical nuclei entrained within a complex neuronal network (Everitt and Robbins, 1997). The mutually interacting PFC and hippocampus (Hipp) represent the core of this network involved in cognitive processing (GoldmanRakic, 1995;Thierry et al, 2000;Warburton and Brown, 2010).…”
Section: Introductionmentioning
confidence: 99%